The Quality Analysis of SIINas Information System in Jakarta Using Technology Acceptance Model Method - Fauzan Mahardika; Yuli Karyanti (Kresnamedia Publisher, 2025)
This study aims to evaluate the service quality of the National Industrial Information System (SIINas) application as a reporting medium for industrial companies to the Ministry of Industry of the Republic of Indonesia. The evaluation was conducted using the Technology Acceptance Model (TAM) approach analyzed through the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS) using SmartPLS. This model tests the relationship between four main constructs, namely Perceived Ease of Use, Perceived Usefulness, Behavioral Intention, and Use Behavior. Data were collected from 188 companies in the DKI Jakarta area that use the SIINas application through a Likert-based questionnaire. The test results show that Perceived Ease of Use has a significant effect on Perceived Usefulness (β = 0.902; p = 0.000) and Behavioral Intention (β = 0.383; p = 0.018), while Perceived Usefulness also has a significant effect on Behavioral Intention (β = 0.487; p = 0.02). Furthermore, Behavioral Intention has a positive influence on Use Behavior (β = 0.189; p = 0.003). However, the R² value for the Use Behavior construct is only 0.036, indicating a low level of variation explained by the model. This finding suggests that perceived usefulness and ease of use contribute to user intention, but do not fully impact actual usage behavior.